Given the function `y=cos(sqrt(sin(tan(pi x))))` . We have to find the derivative.

Let us begin,

`(dy)/(dx)=-sin(sqrt(sin(tan(pi x)))).d/(dx)[sqrt(sin(tan(pi x)))] ------>(1)`

Now,

`d/(dx)[sqrt(sin(tan(pi x)))]=1/(2sqrt(sin(tan(pi x)))).d/(dx)[sin(tan(pi x))] ----->(2)`

Again,

`d/(dx)[sin(tan(pi x))]=cos(tan(pi x))d/(dx)[tan(pi x)]-------->(3)`

`=cos(tan(pi x)). pi sec^2(pi x)`

Now substituting this in (2) we get,

`d/(dx)[sqrt(sin(tan(pi x)))]=1/(2sqrt(sin(tan(pi x)))).cos(tan(pi x)).pi sec^2(pi x)`

Substituting this...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given the function `y=cos(sqrt(sin(tan(pi x))))` . We have to find the derivative.

Let us begin,

`(dy)/(dx)=-sin(sqrt(sin(tan(pi x)))).d/(dx)[sqrt(sin(tan(pi x)))] ------>(1)`

Now,

`d/(dx)[sqrt(sin(tan(pi x)))]=1/(2sqrt(sin(tan(pi x)))).d/(dx)[sin(tan(pi x))] ----->(2)`

Again,

`d/(dx)[sin(tan(pi x))]=cos(tan(pi x))d/(dx)[tan(pi x)]-------->(3)`

`=cos(tan(pi x)). pi sec^2(pi x)`

Now substituting this in (2) we get,

`d/(dx)[sqrt(sin(tan(pi x)))]=1/(2sqrt(sin(tan(pi x)))).cos(tan(pi x)).pi sec^2(pi x)`

Substituting this in (1) we get,

`(dy)/(dx)[cos(sqrt(sin(tan(pi x))))]=-sin(sqrt(sin(tan(pi x)))).pi/(2sqrt(sin(tan(pi x)))).cos(tan(pi x))sec^2(pi x)`